Абсолютна частота як один з критеріїв визначення антонімів - Гончарук, Світлана Вікторівна; Honcharuk, S. V. (Волин. нац. ун-т ім. Лесі Українки, 2011)
У статті досліджено кількісні характеристики просторово-часових прислівників-антонімів. Автор аналізує абсолютні частоти членів антонімічних пар за допомогою статистичних методів. Визначено, що абсолютна частота є основним параметром розмежування членів антонімічних пар. The article is devoted to the investigation of quantitative characteristics of spatio-temporal adverbs-antonyms. The author analyses absolute frequencies of the members of antonymous pairs with the help of statistical methods. It is determined that absolute frequency is the main parameter of differentiating the members of antonymous pairs.
Absolute frequency as one of the criteria of distinguishing antonyms.
Keywords: абсолютна частота; absolute frequency; хі-квадрат; chi-square; кореляційний аналіз; correlation analysis